Problematika Yuridis Dalam Perjanjian Kerja Outsourcing - Elfiani elfiani (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
In the business world competition, it requires the companies to focus on core business. Therefore the supporting work handed over to the other companies as a jobs recipient companies through an chartering agreement jobs. The implementation of this chartering jobs is called outsourcing system. There are three parties to this agreement, employer firms, employment services company and the workers. In this case, there is a working relationship between workers with the employment services company, but the workers doing work on employer firms. The system is on the favorable side to the employer firms, because it can be increase the effectiveness and efficiency. However in the other side, the large number of the labor force jobs, and low competence of workers resulting in their low bargaining position, their rights are tend not to get protection. Beside that, the absence of specific legal instruments that regulate the outsourcing system, and the absence of sanctions for violations of the provisions about employment agreement, can also bring up the labor dispute. For that, there needs to be rules and assertive sanctions to protect the rights of workers.